2018
DOI: 10.1029/2018ja025645
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of Dayside and Nightside Field‐Aligned Current Response to Changes in Solar Wind‐Magnetosphere Coupling

Abstract: Principal component analysis is performed on Birkeland or field‐aligned current (FAC) measurements from the Active Magnetosphere and Planetary Electrodynamics Response Experiment, to determine the response of dayside and nightside FACs to reversals in the orientation of the interplanetary magnetic field (IMF) and the occurrence of substorms. Dayside FACs respond promptly to changes in IMF BY, but the nightside response is delayed by up to an hour and can take up to 4 hr to develop fully, especially during nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 54 publications
8
38
0
Order By: Relevance
“…These time scales are in agreement with Milan et al. (2018), who used principal component analysis and reported that NBZ currents typically take between 45 and 90 min to fully develop. In comparison, McPherron et al.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These time scales are in agreement with Milan et al. (2018), who used principal component analysis and reported that NBZ currents typically take between 45 and 90 min to fully develop. In comparison, McPherron et al.…”
Section: Discussionsupporting
confidence: 91%
“…We can note two main features from our model's response to the “simulated” substorm interval. First, we find that the nightside currents intensify and expand, in immediate response to a drop in SML index and later subside during the “simulated” recovery phase, beginning at T Pred = 40 min, as expected during a substorm interval due to an increase in nightside reconnection rate (Clausen, Milan, et al., 2013; Milan et al., 2018). Second, we find an increase in the area of the polar cap/R1‐oval indicating an increase (Clausen, Baker, et al., 2013) after the onset of a substorm, which later recedes back to its original state during the recovery phase.…”
Section: Observationssupporting
confidence: 70%
See 2 more Smart Citations
“…This is the well‐known directly driven response of the electrojets to the IMF (Kamide & Kokubun, ). At longer lags, we find that the DP2 and DP1 responses are more strongly correlated to the IMF variations than the initial response, despite being presumably less directly driven (e.g., Milan et al, ; Weimer, ). This seems counterintuitive but can be explained via an ionospheric conductivity feedback.…”
Section: Discussionmentioning
confidence: 73%